La inteligencia emocional en docentes del área de comunicación en instituciones educativas urbanas de secundaria de la UGEl Maynas, Iquitos 2024 - Perez Panduro, Karina (2025)
The general objective of this research is to describe emotional intelligence in teachers in the area of communication in urban secondary educational institutions of the UGEL Maynas, Iquitos 2024. The study is descriptive in nature, and its purpose is to present the event studied. The research design is cross-sectional, because the event is studied at a single point in time. The study group is made up of 81 teachers from the communication area of the urban secondary educational institutions of the UGEL Maynas, Iquitos 2024, who were administered a survey on emotional intelligence, composed of a 24 item questionnaire, previously validated by experts. The results indicate that 82.7% of teachers in the area of communication of the urban secondary educational institutions of the UGEL Maynas, reach a Good level of emotional intelligence; 13.7% have a Regular level; and only 3.7% reach the Very Good level.